Carbon Paste as a Candidated Electrode Substrate for Electrochemical Polymerization of 2,5-Dimethylaniline - OJANI, REZA; RAOOF, JAHAN-BAKSH; AHMADY, ATIYE; REZA HOSSEINI, SAYED (Asian Journal of Chemistry, 2010)
A novel method of generating a rapidly reproducible poly(2,5- dimethylaniline)-coated electrode surface is represented. This involves electropolymerization at monomer-modified carbon paste electrode (MCPE). The electropolymerization was accomplished by three methods: potentiodynamic, potentiostatic and galvanostatic methods. The electrochemical behaviour of polymer was studied at different rates of potential scanning at different pH. The electrochemical behaviour indicates that the poly(2,5-dimethylaniline)/MCPE is stable and electroactive. Present investigations show that Ip for polymer prepared by potentiodynamic method is significantly higher than Ip for the polymers prepared by other methods. It is also found out that the electrochemical response of poly(2,5-dimethylaniline) prepared at the surface of carbon paste electrode is better than its response at the surface of glassy carbon electrode with equal geometric area. The electrocatalytic ability of this polymer containing Ni for electro-oxidation of methanol was demonstrated.